An exploratory study of Palestinian science teachers' views of the nature of science - Khaldi, Mousa M. M. (2010)
This mixed methods study investigates Palestinian science teachers' views of the nature of science (NOS), with an in-depth exploration of the nature, causes and context of these views, and the possible reasons why teachers hold such views. The research provides suggestions of possible ways to improve Palestinian science teachers' views of NOS, and the factors within the Palestinian context that might either facilitate or hamper efforts to promote teachers' understanding of NOS.